Dendritic Cells and T Cells, Partners in Atherogenesis and the Translating Road Ahead - Sun, Li; Zhang, Wenjie; Zhao, Yanfang; Wang, Fengge; Liu, Shan; Liu, Lei; Zhao, Lin; Lu, Wei; Li, Minghui; Xu, Yuekang (Frontiers in Immunology, 2020)
Atherosclerosis is a chronic process associated with arterial inflammation, the accumulation of lipids, plaque formation in vessel walls, and thrombosis with late mortal complications such as myocardial infarction and ischemic stroke. Immune and inflammatory responses have significant effects on every phase of atherosclerosis. Increasing evidence has shown that both innate and adaptive “arms” of the immune system play important roles in regulating the progression of atherosclerosis. Accumulating evidence suggests that a unique type of innate immune cell, termed dendritic cells (DCs), play an important role as central instigators, whereas adaptive immune cells, called T lymphocytes, are crucial as active executors of the DC immunity in atherogenesis. These two important immune cell types work in pairs to establish pro-atherogenic or atheroprotective immune responses in vascular tissues. Therefore, understanding the role of DCs and T cells in atherosclerosis is extremely important. Here, in this review, we will present a complete overview, based on existing knowledge of these two cell types in the atherosclerotic microenvironment, and discuss some of the novel means of targeting DCs and T cells as therapeutic tactics for the treatment of atherosclerosis.